The Effects of Conceptual Knowledge Goal Intervention on the Development of Poor Readers’ Reading Comprehension - Guozhong Luo; Wen Li; Bingqing Gong; Yukun Wu (SAGE Open)
Conceptual knowledge goal (CKG) is a typical component of outcome-based learning. However, the contribution of CKG to poor readers’ reading comprehension development remains unclear. Following the suggestion of the Simple View of Reading theory for the poor reader category, the current study recruited 90 poor decoders (PD), 76 poor comprehenders (PC), and 100 general poor readers (GPR) to be randomly divided into CKG and control conditions. After a 12-week intervention, readers who received the CKG condition performed significantly better in character reading and receptive vocabulary than control condition readers, regardless of the reader category. Only PDs who received CKG performed significantly better in listening comprehension than those in the control condition. The results indicate that CKG is an effective approach for educators to enhance the reading comprehension abilities of poor readers in primary schools.